PENGARUH ETOS KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA INDUSTRI KERUPUK AS-SYIFA KOTA BENGKULU - Lidya Puspita Sari; Islamuddin Islamuddin; Meilaty Finthariasari (UM. Bengkulu, 2020)
This study aims to determine the effect of work ethic and work environment on employee work productivity in the As-Syifa cracker industry in Bengkulu City. The research was conducted on Bengkulu City As-Syifa Crackers Employees, the population used in this study were employees who worked on the Bengkulu City As-Syifa Crackers Industry, the number of samples used was 33 respondents, using census techniques. Data that has been collected is processed by using Multiple Linear Regression Analysis Techniques, Determination Coefficient Analysis (R2), and Partial Test (t Test), Simultaneous Test (Test f). From the results of this study indicate that partially Work Ethic has a significant effect on Employee Work Productivity with a value of Î± = 0,000, and the Work Environment has a significant effect on Employee Productivity with a value of Î± = 0.017, While the Work Ethic f Test (X1) and Work Environment (X2) has a significant influence on Employee Productivity (Y) in the As-Syifa Crackers Industry in Bengkulu City. An overall significant level of Î± = 0,000. And has a regression equation Y = 2,999 + 0.370 (X1) + 0.438 (X2). And the coefficient of determination (R2) Adjusted R Square value is 0.838. Where the coefficient of determination means that jointly the Work Ethic and Work Environment contribute to influencing Employee Work Productivity in the As-Syifa Crackers Industry in Bengkulu City. And the most dominant factor with the greatest regression coefficient value is the Work Environment variable (X2) with a value = 0.438. Keywords : Work Ethic, Work Environment, and Employee Work Productivity.